Nonmotor Symptoms Affect Sleep Quality in Early-Stage Parkinson's Disease Patients With or Without Cognitive Dysfunction - Zhu, Jun; Zhong, Min; Yan, Jun; Jiang, Xu; Wu, Zhuang; Pan, Yang; Shen, Bo; Zhang, Lili; Dong, Jingde; Zhang, Li (Frontiers in Neurology, 2020)
Abstract Purpose: Parkinson's disease (PD) patients frequently present with sleep disorders. This study was designed to assess the impact of nonmotor symptoms (NMSs) on sleep quality in early-stage PD patients with and without cognitive dysfunction. Materials and Methods: A sample of 389 early-stage PD patients (modified Hoehn and Yahr score ≤2.5, duration ≤5 years) was recruited for the present study. The Non-Motor Symptoms Questionnaire (NMS-Quest) was used to screen for global NMSs. Depressive symptoms were assessed using the Hamilton Rating Scale for Depression (HAMD). PD motor symptoms were measured with the Unified PD Rating Scale (UPDRS), part III. The Montreal Cognitive Assessment (MoCA) was used to evaluate global cognitive status, and the PD Sleep Scale (PDSS) was used to quantify sleep quality. Polysomnography (PSG) was used for objective assessment of sleep. Results: In our sample, approximately one-quarter of the PD patients suffered from sleep disturbances (23.7%). Our results also confirmed the high prevalence of cognitive dysfunction in patients with PD (39.8%). In patients with cognitive dysfunction, higher percentage of sleep disorders (34.8% vs 16.2%, P< 0.01) was observed. They also with lower PDSS score, sleep efficiency (SE) and longer sleep lantency (SL) and wake after sleep onset (WASO) (All P< 0.05). In total, the patients who suffered from NMSs, such as depressive symptoms, anxiety symptoms, urinary tract symptoms and hallucinations/delusions, had poorer sleep quality. Better cognition may predict better sleep quality. In patients with cognitive dysfunction, the NMS-Hallucinations/delusions score was the most important risk factor for sleep disorders. In patients without cognitive dysfunction, NMSs such as anxiety and cognition and medication were related to sleep disorder. Conclusions: NMSs in early-stage PD are highly associated with and are determinants of subjective sleep quality. Future studies should focus on elucidating the pathophysiology of these symptoms.